2017
DOI: 10.1037/abn0000273
|View full text |Cite
|
Sign up to set email alerts
|

Examination of real-time fluctuations in suicidal ideation and its risk factors: Results from two ecological momentary assessment studies.

Abstract: Two studies examined 2 important but previously unanswered questions about the experience of suicidal ideation: (a) How does suicidal ideation vary over short periods of time?, and (b) To what degree do risk factors for suicidal ideation vary over short periods and are such changes associated with changes in suicidal ideation? Participants in Study 1 were 54 adults who had attempted suicide in the previous year and completed 28 days of ecological momentary assessment (EMA; average of 2.51 assessments per day; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
531
9
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 597 publications
(586 citation statements)
references
References 46 publications
43
531
9
3
Order By: Relevance
“…A study of this magnitude would be enhanced by a longitudinal design; indeed, the cross-sectional nature of the present study minimizes the causal inferences that can be made. The cross-sectional data also do not capture the fluidity of suicide risk [72] or its risk factors [73], hampering our ability to identify AS cognitive concerns as a potential acute warning sign for suicide risk. Finally, although this study was the first study, to our knowledge, of the depression-distress amplification model to employ the CES-D, a gold standard measure of depression symptoms, future research may benefit from more nuanced assessments of depression (e.g., semi-structured clinical interview).…”
Section: Discussionmentioning
confidence: 99%
“…A study of this magnitude would be enhanced by a longitudinal design; indeed, the cross-sectional nature of the present study minimizes the causal inferences that can be made. The cross-sectional data also do not capture the fluidity of suicide risk [72] or its risk factors [73], hampering our ability to identify AS cognitive concerns as a potential acute warning sign for suicide risk. Finally, although this study was the first study, to our knowledge, of the depression-distress amplification model to employ the CES-D, a gold standard measure of depression symptoms, future research may benefit from more nuanced assessments of depression (e.g., semi-structured clinical interview).…”
Section: Discussionmentioning
confidence: 99%
“…In two recent studies using real‐time monitoring to observe suicidal thoughts, our group (Kleiman et al., ) and others (Hallensleben et al., ) found that thoughts of suicide vary considerably over short periods of time (e.g., hour to hour). Here we examine whether there are distinct profiles or subtypes of suicidal thinking by examining hour‐to‐hour changes in the reports of suicidal thoughts over the span of several weeks.…”
Section: Introductionmentioning
confidence: 93%
“…Historically, such an approach has not been possible in the study of suicidal thoughts and behaviors because they occur privately and episodically in a person's life, outside of the scope of standard psychological assessment methods. Moreover, the tools used to assess suicidal thoughts have been until now limited to intermittent assessments separated by weeks, months, or years, which does not address the fact that suicidal thoughts can be highly variable over a few hours (Bagge, Littlefield, Conner, Schumacher, & Lee, ; Kleiman et al., ) and that suicide attempts can occur in response to rapidly escalating thoughts over time periods as short as a day (Millner, Lee, & Nock, ). However, recent advances in smartphone‐based real‐time monitoring technology (i.e., ecological momentary assessment [EMA]) (Shiffman, Stone, & Hufford, ) have made it possible for the first time to overcome these limitations by allowing individuals to report on suicidal thoughts as they naturally occur in a variety of settings (e.g., over the course of clinical care, in a person's day‐to‐day life), which has been done in a small handful of studies to date (for review, see Kleiman & Nock, ).…”
Section: Introductionmentioning
confidence: 99%
“…large representative samples) or through the implementation of real‐time monitoring with smaller high‐risk samples (Glenn & Nock, ). Relevant to the latter, recent work in Ecological Momentary Assessment (EMA) suggests that monitoring suicidal thoughts multiple times a day shows the high variability and short‐term volatility of this clinical outcome, and the importance of monitoring risk factors within similar short‐term time frames (Kleiman et al., ). The ubiquity of smartphone and mobile technology use introduces a rich source of real‐time data that may also help identify a variety of short‐term behavioral signatures of suicide risk (i.e.…”
Section: Treatment Of Suicidal Behaviormentioning
confidence: 99%